ANALISIS PENGARUH PENGGUNAAN MEDIA PEMBELAJARAN DIGITAL DENGAN MINAT BELAJAR SISWA JURUSAN AUDIO VIDEO SMKN 4 MEDAN - Ashari, Novialdi; Pane, Muhammad Akbar Syahbana; Saleh, Khairul (Program Studi Pendidikan Guru Sekolah Dasar Universitas Nahdlatul Ulama Sumatera Utara, 2025)
This study aims to examine the influence of digital learning media on students’ learning interest in the Audio Video Department at SMK Negeri 4 Medan. The integration of digital media in vocational education has become increasingly essential, especially for subjects that require strong visual representation and practical demonstrations. Digital media such as instructional videos, animations, interactive simulations, and multimedia platforms are expected to enhance students’ engagement and comprehension of technical concepts. However, students’ learning interest does not always respond uniformly to the use of digital media, indicating the need for empirical investigation in this context. This research employed a quantitative correlational design with a sample of 30 students selected through cluster sampling. A Likert-scale questionnaire consisting of 12 validated and reliable items was administered to measure both the use of digital learning media and students’ learning interest. Data analysis included descriptive statistics, item validity testing, reliability testing using Cronbach Alpha, and Pearson correlation analysis. The findings revealed that the use of digital learning media among students was categorized as high (mean = 3.97), and students’ learning interest also fell into the high category (mean = 3.90). The reliability coefficient of 0.706 indicated acceptable internal consistency of the instrument. Furthermore, the Pearson correlation test produced a coefficient of r = 0.64 with p < 0.05, demonstrating a positive and significant relationship between the two variables. These results suggest that the effective integration of digital learning media contributes substantially to enhancing students’ learning interest, particularly in vocational fields that heavily rely on visual and practical learning processes. The study underscores the importance of optimizing digital media usage to improve the quality of teaching and learning in vocational education.